Durabilitas Beton Aspal Terhadap Air Hujan - Amal Risky Harahap; Sugeng Wiyono; Elizar Elizar; Anas Puri (Center for Research and Community Service (LPPM) University of Abulyatama, 2022)
The road is designed in order to achieve the service life of the plan, but the fact on the ground many roads suffered damage before the life of the plan service was reached. Environmental factors such as high rainfall with poor drainage conditions can cause puddles on the pavement surface of the road. Standing water for a long duration and plus the load of traffic at the point of standing water on the road surface can cause damage to the road. The purpose of research how the durability value and characteristics of asphalt concrete due to rainwater soaking. Experimental research methods are laboratoryized with the Cantabro method under long-term process conditions (Long Term Oven Agin (LTOA)). Test objects that have undergone the LTOA process are then soaked with rainwater and test Marshall's characteristics. Irs value of rainwater soaking duration of 7 days by 63%, IDP value of 32% and IDK of 30%. Marshall's characteristic value decreased as the duration of rainwater soaking increased. The lowest stability value of rainwater soaking duration of 7 days amounted to 1852 kg and the highest stability value without soaking of 3015 kg.